Approach to orthopaedic trauma and limb reconstructive surgery - Mohd. Yusof, Nazri (IIUM Press, 2025)
This book offers a comprehensive overview of the basic science and principles in managing orthopedic trauma, with a distinctive approach to understanding and treating trauma-related conditions. It begins with foundational concepts, including systemic impacts of trauma and national statistics, followed by the essential management of soft tissue injuries-highlighting their crucial role in successful fracture treatment. Fracture management is discussed through principles and classification, with detailed emphasis on complications, particularly fracture-related infections. A dedicated chapter explores surgical techniques using external fixators, the most common implants in acute trauma. The book concludes with clinical methods for addressing late trauma complications. Each chapter also integrates Islamic perspectives relevant to the topic, offering a holistic educational experience.